New Role of P. brasiliensis α-Glucan: Differentiation of Non-conventional Dendritic Cells - Souza, Ana Camila Oliveira; Favali, Cecília; Soares, Naiara Caroline; Tavares, Natalia Machado; Jerônimo, Márcio Sousa; Veloso Junior, Paulo Henrique; Marina, Clara Luna; Santos, Claire; Brodskyn, Cláudia; Bocca, Anamelia Lorenzetti (Frontiers in Microbiology, 2019)
The cell wall has a critical role in the host immune response to fungal pathogens. In this study, we investigated the influence of two cell wall fractions of the dimorphic fungi Paracoccidioides brasiliensis (Pb) in the in vitro generation of monocyte-derived dendritic cells (MoDCs). Monocytes were purified from the peripheral blood of healthy donors and cultivated for seven days in medium supplemented with IL-4 and GM-CSF in the presence of Pb cell wall fractions: the alkali-insoluble F1, constituted by β-1,3-glucans, chitin and proteins, and the alkali-soluble F2, mainly constituted by α-glucan. MoDCs phenotypes were evaluated regarding cell surface expression of CD1a, DC-SIGN, HLA-DR, CD80 and CD83 and production of cytokines. The α-glucan-rich cell wall fraction downregulated the differentiation of CD1a+ MoDCs, a dendritic cell subset that stimulate Th1 responses. The presence of both cell fractions inhibited DC-SIGN and HLA-DR expression, while the expression of maturation markers was differentially induced in CD1a- MoDCs. Differentiation upon F1 and F2 stimulation induced mixed profile of inflammatory cytokines. Altogether, these data demonstrate that Pb cell wall fractions differentially induce a dysregulation in DCs differentiation. Moreover, our results suggest that cell wall α-glucan promote the differentiation of CD1a- DCs, potentially favoring Th2 polarization and contributing to pathogen persistence.